Chemical and Sensory Characteristics of Arabica Coffee Due to Variations in Processing Methods and Fermentation Time - Dina Mardhatilah; Kuni Faizah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The natural, full-wash, and honey processing methods, along with fermentation duration, significantly influence the chemical components and flavour profile of the resulting coffee. Therefore, it is essential to conduct research to determine the chemical and flavour characteristics produced by each processing method to maintain quality and ensure flavour consistency. The research design employed is a complete two-factor block design. The first factor is the variation in processing methods: natural, full-wash, and honey. The second factor is fermentation duration: 18 h, 24 h, and 30 h. The analyses performed include moisture content, ash content, pH, lipid content, protein content, total acid content, caffeine content, and sensory evaluation using the SCAA method. The results of this study indicate that variations in processing methods affect the values of moisture content, protein content, caffeine content, lipid content, and total acid content. Similarly, the fermentation duration of coffee cherries affects the moisture content, protein content, caffeine content, lipid content, and total acid content. The study also shows a relationship between the variations in processing methods and the fermentation duration of coffee cherries. The honey processing method and optimal ripeness levels were most preferred by the panelists. All the coffee produced in this study has met the SNI 01-3542-2004 standard.